Bispecific antibody drug conjugates: Making 1+1>2 - Yilin Gu; Zhijia Wang; Yuxi Wang (Elsevier, 2024)
Bispecific antibody‒drug conjugates (BsADCs) represent an innovative therapeutic category amalgamating the merits of antibody‒drug conjugates (ADCs) and bispecific antibodies (BsAbs). Positioned as the next-generation ADC approach, BsADCs hold promise for ameliorating extant clinical challenges associated with ADCs, particularly pertaining to issues such as poor internalization, off-target toxicity, and drug resistance. Presently, ten BsADCs are undergoing clinical trials, and initial findings underscore the imperative for ongoing refinement. This review initially delves into specific design considerations for BsADCs, encompassing target selection, antibody formats, and the linker-payload complex. Subsequent sections delineate the extant progress and challenges encountered by BsADCs, illustrated through pertinent case studies. The amalgamation of BsAbs with ADCs offers a prospective solution to prevailing clinical limitations of ADCs. Nevertheless, the symbiotic interplay among BsAb, linker, and payload necessitates further optimizations and coordination beyond a simplistic "1 + 1" to effectively surmount the extant challenges facing the BsADC domain.